Outcomes of patients with acute respiratory failure on veno-venous extracorporeal membrane oxygenation requiring additional circulatory support by veno-venoarterial extracorporeal membrane oxygenation - Erlebach, Rolf; Wild, Lennart C.; Seeliger, Benjamin; Rath, Ann-Kathrin; Andermatt, Rea; Hofmaenner, Daniel A.; Schewe, Jens-Christian; Ganter, Christoph C.; Müller, Mattia; Putensen, Christian; Natanov, Ruslan; Kühn, Christian; et al. (Frontiers in Medicine, 2022)
Objective Veno-venous (V-V) extracorporeal membrane oxygenation (ECMO) is increasingly used to support patients with severe acute respiratory distress syndrome (ARDS). In case of additional cardio-circulatory failure, some experienced centers upgrade the V-V ECMO with an additional arterial return cannula (termed V-VA ECMO). Here we analyzed short- and long-term outcome together with potential predictors of mortality. Design Multicenter, retrospective analysis between January 2008 and September 2021. Setting Three tertiary care ECMO centers in Germany (Hannover, Bonn) and Switzerland (Zurich). Patients Seventy-three V-V ECMO patients with ARDS and additional acute cardio-circulatory deterioration required an upgrade to V-VA ECMO were included in this study. Measurements and main results Fifty-three patients required an upgrade from V-V to V-VA and 20 patients were directly triple cannulated. Median (Interquartile Range) age was 49 (28–57) years and SOFA score was 14 (12–17) at V-VA ECMO upgrade. Vasoactive-inotropic score decreased from 53 (12–123) at V-VA ECMO upgrade to 9 (3–37) after 24 h of V-VA ECMO support. Weaning from V-VA and V-V ECMO was successful in 47 (64%) and 40 (55%) patients, respectively. Duration of ECMO support was 12 (6–22) days and ICU length of stay was 32 (16–46) days. Overall ICU mortality was 48% and hospital mortality 51%. Two additional patients died after hospital discharge while the remaining patients survived up to two years (with six patients being lost to follow-up). The vast majority of patients was free from higher degree persistent organ dysfunction at follow-up. A SOFA score > 14 and higher lactate concentrations at the day of V-VA upgrade were independent predictors of mortality in the multivariate regression analysis. Conclusion In this analysis, the use of V-VA ECMO in patients with ARDS and concomitant cardiocirculatory failure was associated with a hospital survival of about 50%, and most of these patients survived up to 2 years. A SOFA score > 14 and elevated lactate levels at the day of V-VA upgrade predict unfavorable outcome.